An Indian Encounter: A Conversation with Jeannette Armstrong - Srivastava, Prem Kumari (Studies in Canadian Literature, 2012)
Jeannette Armstrong is an internationally recognized writer, teacher, artist, sculptor, and activist for Indigenous rights. Here, in robust detail, she describes her role and identity as a cultural archivist and knowledge keeper of the Okanagan – work she carries on in the tradition of her great aunt, Mourning Dove (Hum-Ishu-Ma), and that she has viewed as an academic responsibility since her teen years. Looking back to 1986, she discusses her founding vision of the En’owkin Centre in Penticton, British Columbia, a retreat where Indigenous artists and academics continue to work collaboratively towards the recovery of language and culture. In this conversation, Armstrong offers her views on the marginalization of Aboriginal cinema in Canada, the nature of the western canon, Okanagan oral literatures, and the mobilization of Indigenous systems of knowledge. In the context of the world’s current environmental crisis, Armstrong identifies an urgent need for increased attention to Indigenous perspectives.